Exploring cultural orientation on the entrepreneur competencies in the globalization era - Mira Rochimi Mutiara; Ina Primiana; Joeliaty Joeliaty; Martha Fani Cahyandito (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The existence of globalization concept absolutely brings consequences for business environment. Based on international literature, cultural orientation was required on business management in the globalization era. Nevertheless, there have been few numbers of cross-cultural entrepreneurship research. Previous research tended to focus on discussing cultural dimensions or using them in entrepreneurship. Therefore, this study proposes a different perspective which is to explore the cultural dimensions for the formation of entrepreneur competencies. Thus, this study aims at suggesting conceptual models and providing empirical evidence concerning national and individual cultural orientation including its role in influencing the formation of Small and Medium Enterprises (SMEs) entrepreneur competencies in facing the globalization era. For this purpose, the survey questionnaire was distributed to 129 SMEs entrepreneurs in the fashion sector in West Java - Indonesia, which was then tested by using VSM 1994 Formula, SPSS method and Partial Least Square (PLS) method. The findings and originality of this study were the novelty of national and its individual cultural values for Indonesia. Moreover, this study discovered that Cultural Orientation significantly influenced the form of entrepreneur competencies. Thus, the role of cultural orientation cannot be ignored in enhancing the ability of SMEs entrepreneurs to face the globalization era.
Keywords: L26; M16; O15; 650; Small and Medium Enterprises (SMEs); cultural orientation; national culture; individual cultural; entrepreneur competencies; globalization